Energy Efficiency for Florida Aquaculture Facilities: Variable Frequency Drives - Jordan Neff; Eric Cassiano; Micah Alo; Craig Watson (EDIS)
Energy consumption is often a primary contributor to the cost of operation in aquaculture. Even on a moderately sized farm, excessive energy consumption can be a limiting factor in the success of an aquaculture business. Reducing operational costs can increase total profitability. Identifying inefficient energy use and implementing energy-efficient technologies can help reduce the total cost of operation. This publication is one in a series that details techniques and methods for reducing energy consumption to decrease operational costs on aquaculture facilities.